2008
DOI: 10.1007/s10722-008-9379-x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among Avena species as revealed by consensus chloroplast simple sequence repeat (ccSSR) markers

Abstract: Consensus chloroplast simple sequence repeat (ccSSR) makers were used to assess the genetic variation and genetic relationships of 80 accessions from 25 taxa of the genus Avena. Fifteen out of 16 ccSSR markers (93.75%) were polymorphic. A total of 51 alleles were detected at the 16 ccSSR loci. The number of alleles per locus ranged from 1 to 6, with an average of 3.2 alleles. Among these ccSSR loci, the highest polymorphism information content (PIC) value was 0.754, while the lowest PIC value was 0. The mean g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 83 publications
2
10
0
Order By: Relevance
“…Furthermore, this might provide one explanation for the lack of differentiation between the AC and ACD sequences into separate clades. of the clones of A. damascena and A. fatua , indicating the close relationship between these two species, which is in agreement with the results of in situ hybridization ( JELLEN et al 1994a;LEGGETT and MARKHAND 1995) and with the study using ccSSR ( LI et al 2009). Recently using chloroplast sequences to investigate the maternal donor of the polyploid, we found that A. damascena is closely related to A. fatua (Wei et al unpubl.).…”
Section: Phylogenetic Inferences In Avena Based On Its Sequencessupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, this might provide one explanation for the lack of differentiation between the AC and ACD sequences into separate clades. of the clones of A. damascena and A. fatua , indicating the close relationship between these two species, which is in agreement with the results of in situ hybridization ( JELLEN et al 1994a;LEGGETT and MARKHAND 1995) and with the study using ccSSR ( LI et al 2009). Recently using chloroplast sequences to investigate the maternal donor of the polyploid, we found that A. damascena is closely related to A. fatua (Wei et al unpubl.).…”
Section: Phylogenetic Inferences In Avena Based On Its Sequencessupporting
confidence: 90%
“…They also provided evidence that in the polyploids the nuclear genome of maternal origin undergoes fewer changes with time than the nuclear genome of paternal origin. In Avena the ITS sequences of the A and C genomes might have diverged in a similar fashion and since the A genome was determined as the maternal donor of AACC tetraploids (Nishiyama and Yabuno 1975; Leggett 1984; Nishiyama 1984; Murai and Tsunewaki 1987; Rines et al 1988; Nikoloudakis and Katsiotis 2008; Li et al 2009; Peng et al unpubl. ), it has undergone fewer mutational changes than the paternal donor, the C‐genome.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with the results of ccSSR markers (Li et al 2009) and matK gene sequences (Peng et al 2010b). In situ hybridization (Jellen et al 1994;Yang et al 1999;Shelukhina et al 2008) also provides evidence for the close relationship between these two species.…”
Section: Relationships Among Avena Speciessupporting
confidence: 92%
“…Fourn., Pseudarrhenatherum Rouy, Rostraria Trin., Sphenopholis Scribn., Trisetaria Forssk., Tricholemma (Röser) Röser, Trisetopsis Röser & Wölk, Trisetum Pers., Tzveleviochloa Röser & A. Wölk and × Trisetopsotrichon Röser & A. Wölk. Of these, the best studied genus is Avena (oats) (Drossou et al 2004, Peng et al 2008, 2010a, 2010b, Li et al 2009, Yan et al 2014). Several studies have identified Helictotrichon s.l.…”
Section: Introductionmentioning
confidence: 99%